Reflexões sobre o habitus escolar de alunos do ensino fundamental I em seu processo de escolarização - Martins, Daniela Gimenez Faustino (Universidade Federal de São Carlos, 2018)
This study aims to study the school habitus of elementary school students in a municipal school. The research is inserted in the discussions about the schooling process, more specifically, in the relation that is established between the school habitus, the practices of teachers and the family of students. The research problem investigates the contribution of the homework mediated by the family and school in the constitution of the school habitus of elementary school students and their contribution for the students' schooling process? The general objective of this research is therefore to analyze the school habitus of elementary school students in a municipal school in the outskirts of the city Serrana – SP, in order to understand their family and school relations with the students' schooling process. It is intended to identify in the routines, in the relations between the family and school institution, the strategies and practices that contribute to the dynamic consolidation of the school habitus. It seeks to identify and reflect on the possible existence of discipline, routines and arrangements for student studies within and outside the school environment and whether families and teachers enable practices that teach these students to study, promoting a school habitus and cultural capital school profitable. The research is based on the concept of habitus of the sociological theory of Pierre Bourdieu. For the collection of data, semi-structured interviews were conducted with teachers, parents or guardians of students and with students enrolled in a municipal elementary school. A total of 14 participants were interviewed. The data of the interviews were submitted to the content analysis and the results show that most of the students have dispositions for the studies, doing with certain frequency the activities inside and outside the school environment, but the routines and discipline established by the families are presented basically by through the development of homework, proposed by the teacher, with some family practices that teach them to study. However, despite their limitations on the possibility of school aid to children, families demonstrate the importance of these practices in the formation of their children / grandchildren. The data also indicate that the teachers believe that these dispositions, discipline and routines for the studies that make up the school habitus have an impact on the students' school performance, and present strategies in their pedagogical practices aiming at the consolidation of this habitus that has been demonstrated related to the students' profitability.
Reflections on the educational habitus of elementary school students in their schooling process
Keywords: Habitus escolar; Processo de escolarização; Ensino fundamental I; School habitus; Educational process; Elementary school I; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO